2010
DOI: 10.1080/09687769.2010.529109
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing online distance education in small rural US schools: a hybrid, learner-centred model

Abstract: Online distance education (ODE) has become pervasive and can potentially transform pedagogical practices across primary, secondary and university-based educational systems. ODE is considered a flexible option for non-traditional students such as adult learners and home-schoolers, and a convenient way to deliver remedial courses. ODE is also a feasible and attractive option for rural schools, which educate 29% of all K-12 students in the United States, and often struggle to provide advanced courses and attract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Online learning has been considered a useful tool for learning, cost-effectiveness, flexibility, and the possibility of providing world-class education (Jeffcoat Bartley and Golek, 2004;Gratton-Lavoie and Stanley, 2009;De La Varre et al, 2010). A study by Li and Lalani (2020) indicated that COVID-19 had brought change to the status of learning in the 21st century.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online learning has been considered a useful tool for learning, cost-effectiveness, flexibility, and the possibility of providing world-class education (Jeffcoat Bartley and Golek, 2004;Gratton-Lavoie and Stanley, 2009;De La Varre et al, 2010). A study by Li and Lalani (2020) indicated that COVID-19 had brought change to the status of learning in the 21st century.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Limited internet access which includes poor internet connection and low speed demotivate institutions for pursuing online education (Sinha & Bagarukayo, 2019 ). Rural communities involved in online learning find it difficult to fund and attract qualified teachers to instruct advanced courses (de la Varre, Keane, & Irvin, 2010 ). Lack of internet access and computers in homes in rural areas affect the progress of online learning (DePaul, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many students have engaged in online learning, either completely online or via hybrid modes that combine face-to-face and online instruction (Bradford and Wyatt, 2010). Several factors have contributed to online education's rising popularity, including its perceived efficacy as a learning tool, its low cost, flexibility and the promise of delivering the best education to students worldwide (Jeffcoat Bartley and Golek, 2004;Gratton Lavoie and Stanley, 2009;De La Varre et al, 2010;Dubey and Sahu, 2021, 2022, 2022a. Li and Lalani's (2020) research found that COVID-19 has altered the trajectory of education in the 21st century.…”
Section: Theoretical Grounding and Hypotheses Developmentmentioning
confidence: 99%